Uptake of soil‐applied thiamethoxam in orange and its effect against Asian citrus psyllid in different seasons. Issue 5 (7th December 2018) - Hu, Wei; Kuang, Fan; Chun, Jiong; Lu, Zhanjun; Li, Xingtao; Zhao, Qiyang; Zhong, Balian; Su, Huanan; Zhang, Zhixiang; Zhang, Ning
Abstract: BACKGROUND: Asian citrus psyllid (ACP), Diaphorina citri Kuwayama, is an important pest of citrus worldwide because it transmits the bacteria causing huanglongbing (HLB). We investigated the effects and persistence of two soil application rates of thiamethoxam on ACP populations in two flushing seasons in the field. Thiamethoxam and clothianidin residues in the fruit were detected to evaluate food safety. RESULTS: Soil application of 50% thiamethoxam water‐dispersible granules at concentrations of 4 and 10 g tree −1 significantly decreased ACP populations, and there was a positive correlation between control efficacy and the persistence of thiamethoxam and clothianidin in leaves, providing longer‐term protection for up to 90 days in the fall compared with 60 days in the spring. Higher thiamethoxam and clothianidin amounts were observed in new leaves than in old leaves. Thiamethoxam and clothianidin residues at a high rate in fruit were 0.012 and 0.010 mg kg −1 at harvest, respectively, and neither insecticides was detectable at low rates. CONCLUSIONS: These results demonstrate that soil‐applied thiamethoxam plays a role in defending ACP, and provides an extended period of control efficacy. This knowledge could provide a reference for the control of ACP by soil application of thiamethoxam to reduce HLB spread. © 2018 Society of Chemical Industry Abstract : Soil application of thiamethoxam provided an extended period of efficacy to Asian citrus psyllid. Thiamethoxam and clothianidin residues in fruits were below the maximum residue limit in Japan.